Herpes Zoster Infection in Patients With Ulcerative Colitis Receiving Tofacitinib. Issue 10 (30th May 2018) - Winthrop, Kevin L; Melmed, Gil Y; Vermeire, Séverine; Long, Millie D; Chan, Gary; Pedersen, Ronald D; Lawendy, Nervin; Thorpe, Andrew J; Nduaka, Chudy I; Su, Chinyu
Abstract: Background: Tofacitinib is an oral, small molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). Tofacitinib is approved for rheumatoid arthritis and psoriatic arthritis, where it has been shown to increase herpes zoster (HZ) risk. We evaluated HZ risk among UC patients using tofacitinib. Methods: HZ cases were identified in tofacitinib phase II/III/ongoing, open-label, long-term extension (OLE) UC trials. We calculated HZ incidence rates (IRs) per 100 patient-years of tofacitinib exposure within phase III maintenance (Maintenance Cohort) and phase II/III/OLE (Overall Cohort) studies, stratified by baseline demographics and other factors. HZ risk factors were evaluated in the Overall Cohort using Cox proportional hazard models. Results: Overall, 65 (5.6%) patients developed HZ. Eleven patients had multidermatomal involvement (2 nonadjacent or 3–6 adjacent dermatomes), and 1 developed encephalitis (resolved upon standard treatment). Five (7.7%) events led to treatment discontinuation. HZ IR (95% confidence interval [CI]) in the Overall Cohort was 4.07 (3.14–5.19) over a mean (range) of 509.1 (1–1606) days, with no increased risk observed with increasing tofacitinib exposure. IRs (95% CI) were highest in patients age ≥65 years, 9.55 (4.77–17.08); Asian patients, 6.49 (3.55–10.89); patients with prior tumor necrosis factor inhibitor (TNFi) failure, 5.38 (3.86–7.29); and patients using tofacitinib 10 mg twice daily, 4.25 (3.18–5.56). Multivariate analysis identified older age and prior TNFi failure as independent risk factors. Conclusions: In tofacitinib-treated UC patients, there was an elevated risk of HZ, although complicated HZ was infrequent. Increased HZ rates occurred in patients who were older, Asian, or had prior TNFi failure (NCT00787202, NCT01465763, NCT01458951, NCT01458574, NCT01470612).